Studi Etnomatematika Pada Budaya Masyarakat Larantuka (Asimtot : Jurnal Kependidikan Matematika, 2019)
The environment can become a source of learning in a process of mathematical learning related to the real world. One source learning in the environment is cultural. Mathematical lessons that studied educated participants at school are sometimes different to important transatic problems that encountered in everyday life, makes it more difficult learning participants linking the links of furatic concepts  that  are  formal  with  issues  of  culture.  Etnomathematics  connects cultures with mathematics learning. The purpose of this research is to obtain the description of the value of the impostor’s value and growing up to the cultural society of  Waibalun. This type of  research  is a  qualitative research  with  the Etnographic  design.  Data  collection  by  observation,  interviews  and documentation. The subject in this study is three person taken Purposive against public figures who learn and understand well about indigenous homes. The object of this  research is the Waibalun indigenous home. The results of data analysis show that a) Etnomathematical activity in the process of making Waibalun indigenous   homes,   that   is   measuring,   counting   and   designing;   b)   The mathematical values were found in the Waibalun indigenous home consist of, the angle, rectangle, triangle, trapezium, tube and reflections.
Keywords: Etnomathematics; Culture; Indigenous Home